2013
DOI: 10.1590/brag.2013.041
|View full text |Cite
|
Sign up to set email alerts
|

Produção de fitomassa e acúmulo de nutrientes por plantas de cobertura no cerrado piauiense

Abstract: ResumoO objetivo deste trabalho foi avaliar o potencial de plantas de cobertura semeadas em diferentes sistemas de cultivo quanto à produção de fitomassa e acúmulo de nutrientes, no cerrado piauiense. O experimento foi instalado no ano agrícola 2010/2011, na Serra do Quilombo, município de Bom Jesus (Piauí). O arranjo utilizado foi em parcelas subdivididas, com os seguintes sistemas de manejo do solo: preparo convencional e plantio direto avaliados nas parcelas e, nas subparcelas, os sistemas de produção: S 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0
3

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 15 publications
2
13
0
3
Order By: Relevance
“…Most species cultivated as cover crops are either grasses or leguminous plants. Millet ( Pennisetum glaucum ) is one of the most used grasses in the Brazilian Cerrado (Ferreira Junior et al., ) because of its high straw yield (Pacheco et al., , ; Silva Filho, Borin, & Ferreira, ), with an average of 10 t ha −1 (Wutke, Calegari, & Wildner, ), and its high C/N ratio. These attributes promote greater soil protection (Silva Filho et al., ) and increased nutrient cycling (Pacheco et al., , ), even under water deficit conditions (Pacheco et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Most species cultivated as cover crops are either grasses or leguminous plants. Millet ( Pennisetum glaucum ) is one of the most used grasses in the Brazilian Cerrado (Ferreira Junior et al., ) because of its high straw yield (Pacheco et al., , ; Silva Filho, Borin, & Ferreira, ), with an average of 10 t ha −1 (Wutke, Calegari, & Wildner, ), and its high C/N ratio. These attributes promote greater soil protection (Silva Filho et al., ) and increased nutrient cycling (Pacheco et al., , ), even under water deficit conditions (Pacheco et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Although tropical regions face a hard time in straw production, vegetal residue decomposition in these regions is fast due to high temperatures and humidity throughout most of the year. Thus, it is extremely important knowing the amount and permanence time of straws belonging to the species used in rotation or consortium cultures (Pacheco et al, 2013). Lange et al (2009) found that the straw decomposition rate of different species reached 30 kg ha -1 day -1 between May and November (174 days) in Minas Gerais Cerrado region; thus, showing that straw accumulation and maintenance in Cerrado is not an easy task.…”
Section: Introductionmentioning
confidence: 99%
“…Technologies such as no-till cropping (SPD) with tilling only in the planting furrow, crop rotation and use of cover crops (MORETI et al, 2007) are important tools that can promote yield gains and quality with less impact to the environment (PACHECO et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%